2020 IEEE PES Innovative Smart Grid Technologies Europe (ISGT-Europe) 2020
DOI: 10.1109/isgt-europe47291.2020.9248870
|View full text |Cite
|
Sign up to set email alerts
|

A review of P2P energy markets and a possible application for remote areas

Abstract: Peer-to-peer (P2P) markets are emerging as a promising alternative to the current centralized markets, especially for the management and operation of areas where traditionally passive electricity consumers become small-scale producers (prosumers). This solution may also be a more convenient alternative to an expensive extension of the existing grid infrastructure, to handle the increasing electric load. Thus, lately, extensive research work is aiming to provide efficient and reliable operation of local energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…P2P market design [3,8,9, P2P/P2G market design [9,11,16,42,46,[57][58][59][60] P2P design on sector coupling [61][62][63][64] Physical and virtual Layer [3,13,25,34,40,51,56,[65][66][67][68][69][70][71][72][73][74][75][76] Social perspectives [66,71,[77][78][79][80][81][82][83][84][85][86] Policy perspectives [66,77,83,84,86,...…”
Section: Focus/approach/area Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…P2P market design [3,8,9, P2P/P2G market design [9,11,16,42,46,[57][58][59][60] P2P design on sector coupling [61][62][63][64] Physical and virtual Layer [3,13,25,34,40,51,56,[65][66][67][68][69][70][71][72][73][74][75][76] Social perspectives [66,71,[77][78][79][80][81][82][83][84][85][86] Policy perspectives [66,77,83,84,86,...…”
Section: Focus/approach/area Sourcesmentioning
confidence: 99%
“…A Korean test case study for three different MGs performing P2P-P2G transactions using the market clearing price signal is analyzed in [59]. Dudkina E. et al in [57] presented a pure P2G power flow optimization problem for two remote villages physically interconnected between each other.…”
Section: Focus/approach/area Sourcesmentioning
confidence: 99%
“…A review of P2P energy markets with Blockchain technology-based control has shown various alternatives for their implementation. However, to the authors' best knowledge, the P2P market model has not been adequately considered in rural areas [24]. This is primarily due to the continued lack of internet access, which remains a significant obstacle to the promotion of innovative P2P energy sharing solutions.…”
Section: Introductionmentioning
confidence: 99%